Pheno-morphology of two paramo species of Miconia (Melastomataceae): optimization of flowering and fructification to enhance dispersal - Carvajal-Muñoz, Angie Paola; Morales-Puentes, María Eugenia; Gil-Leguizamón, Pablo Andrés; Reyes-Duarte, Andrea Camila (Revista de Biología Tropical, 2022)
Introduction: Paramos are among the ecosystems that are most affected by anthropic activities, increasing the need for phenological studies as a basis for management and conservation. Objective: To describe the pheno-morphology of Miconia ligustrina and Miconia elaeoides. Methods: From September 2019 to February 2020, and from April 2021 to August of the same year, the phenology of 12 individuals of each species was monitored. Additionally, phenological data of herbariums were linked to corroborate obtained results. In the two data sets, distribution of data was described using circular statistics; in addition, we recorded the precipitation and temperature in the area. Additionally, we described the morphometry of each species. Results: The flowering peak of M. ligustrina is in April, and fruiting concentrates between June and July; in M. elaeoides, flowering is massive in January, and the highest fruit production in May. The phenology was correlated with rainfall: flowering takes place in the dry season and fruiting in the rainy season. The species differ morphologically, but, as in other Miconia species, the flowers and fruits are small (approx. 5 mm). Conclusions: Flowering occurs in the dry season and fructification in the rainy season, when the photosynthetic rate is low and frugivory increases. This phenological pattern favors optimal seed dispersal.